Optimal outcome measures for a trial of not routinely measuring gastric residual volume in neonatal care: a mixed methods consensus process. Issue 3 (30th October 2020) - Gale, Chris; Dorling, Jon; Arch, Barbara; Woolfall, Kerry; Deja, Elizabeth; Roper, Louise; Jones, Ashley P; Latten, Lynne; Eccleson, Helen; Hickey, Helen; Pathan, Nazima; Preston, Jennifer; et al.
Abstract : Background: Routine measurement of gastric residual volume to guide feeding is widespread in neonatal units but not supported by high-quality evidence. Outcome selection is critical to trial design. Objective: To determine optimal outcome measures for a trial of not routinely measuring gastric residual volume in neonatal care. Design: A focused literature review, parent interviews, modified two-round Delphi survey and stakeholder consensus meeting. Participants: Sixty-one neonatal healthcare professionals participated in an eDelphi survey; 17 parents were interviewed. 19 parents and neonatal healthcare professionals took part in the consensus meeting. Results: Literature review generated 14 outcomes, and parent interviews contributed eight additional outcomes; these 22 outcomes were then ranked by 74 healthcare professionals in the first Delphi round where four further outcomes were proposed; 26 outcomes were ranked in the second round by 61 healthcare professionals. Five outcomes were categorised as 'consensus in', and no outcomes were voted 'consensus out'. 'No consensus' outcomes were discussed and voted on in a face-to-face meeting by 19 participants, where four were voted 'consensus in'. The final nine consensus outcomes were: mortality, necrotising enterocolitis, time to full enteral feeds, duration of parenteral nutrition, time feeds stopped per 24 hours, healthcare-associated infection; catheter-associated bloodstream infection, change in weight between birth and neonatal discharge and pneumonia due to milk aspiration. Conclusions and relevance: We have identified outcomes for a trial of no routine measurement of gastric residual volume to guide feeding in neonatal care. This outcome set will ensure outcomes are important to healthcare professionals and parents.